2018
DOI: 10.5812/numonthly.83823
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Assisted Extracorporeal Pyeloplasty: A Minimally Invasive Approach to Pediatric Ureteropelvic Junction Obstruction

Abstract: Background: Ureteropelvic junction obstruction (UPJO) is a common congenital anomaly in pediatrics that may require surgical intervention performed by open, laparoscopic-assisted, laparoscopic, or robotic-assisted fashion. Laparoscopic pyeloplasty hasn't become popular due to instrument or skill limitations. Laparoscopic-assisted pyeloplasty could be the first step towards a minimally invasive approach to UPJO in pediatrics. Methods: The current study was conducted on 60 infants with UPJO treated with either l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…Although several studies [12,13] have shown an improvement in split function, we did not find any improvement. Ritchie et al [14] showed that MAG-3 scan can provide DRF at a similar accuracy with Tc-99 m dimercaptosuccinic acid (DMSA).…”
Section: Discussioncontrasting
confidence: 99%
“…Although several studies [12,13] have shown an improvement in split function, we did not find any improvement. Ritchie et al [14] showed that MAG-3 scan can provide DRF at a similar accuracy with Tc-99 m dimercaptosuccinic acid (DMSA).…”
Section: Discussioncontrasting
confidence: 99%